Assessing Remote Social Interaction for Autistic People Using Physiological Signals in a Collaborative Virtual Reality Workplace (Global Journal of Human-Social Science, 2024)
The study focuses on enhancing workplace experiences for autistic people by addressing professional burnout risks. Acknowledging the benefits of sensory adjustments for autistic employees, previous interactions with autistic participants associations and inclusive organizations highlighted challenges in gauging emotional well-being during workplace social dynamics and tasks. This study delves into real-time evaluations centered on collaborative task-based social interactions. The methodological design consists of a Collaborative Virtual Simulation (CVS) specifically crafted for vocational training targeting autistic people. We have implemented a feedback system for real-time monitoring of cognitive stress, mental workload, and emotional self-regulation within the CVS. The assessment of our approach involved analyzing cognitive stress, mental workload, and physiological synchronization of respiratory sinus arrhythmia (RSA), amidst neuroatypical and neurotypical pairs within the CVS.
Keywords: autism; workplace integration; professional burnout; emotional well-being; collaborative virtual simulation (CVS)